2019
DOI: 10.1017/s1930297500003399
|View full text |Cite
|
Sign up to set email alerts
|

The link between intuitive thinking and social conservatism is stronger in WEIRD societies

Abstract: While previous studies reveal mixed findings on the relationship between analytic cognitive style (ACS) and right-wing (conservative) political orientation, the correlation is generally negative. However, most of these studies are based on Western, educated, industrialized, rich, and democratic (WEIRD) societies, and it is not clear whether this relationship is a cross-culturally stable phenomenon. In order to test cross-cultural generalizability of this finding, we re-analyzed the data collected by the Many L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…We followed procedures described in the Many Labs 2 project (i.e., Klein et al, 2018; see also Yilmaz & Alper, 2019) to quantify sample WEIRDness via the sample country of origin (see https://osf .io/b7qrt/for/ more detailed information).…”
Section: Weirdnessmentioning
confidence: 99%
“…We followed procedures described in the Many Labs 2 project (i.e., Klein et al, 2018; see also Yilmaz & Alper, 2019) to quantify sample WEIRDness via the sample country of origin (see https://osf .io/b7qrt/for/ more detailed information).…”
Section: Weirdnessmentioning
confidence: 99%
“…But it was typically the only clue of cultural belonging in the papers, and analyses found that alternative social aggregates (e.g., ethnicity) contributed only negligible explained variance to that already captured by nations (Akaliyski et al, 2021). Depending on the sample's country or region, we also labelled a paper as 'WEIRD', 'non-WEIRD', or 'mixed' based on previous studies' geographical categorizations (Klein et al, 2018;Yilmaz & Alper, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…• meta-analyses of crowd-sourced data (e.g., Yilmaz and Alper (2019); Huber et al (2023)), whereby a core coordination team of researchers invite multiple independent contributors to collaborate on selected research questions. This approach relies on the horizontal distribution of ownership, resources, and expertise, "enabling the conduct of large-scale research projects, democratizing who contributes to science, and assessing the robustness of findings" (Uhlmann et al, 2019);…”
Section: Literature Review and Methodologymentioning
confidence: 99%
“…What is more, in 19 of these 25 manuscripts the authors only control for geographic differences through dummy variables in meta-regressions and subgroup analyses, meaning that any related findings can hardly be interpreted and lots of research opportunities lie in this area. It is unsurprising that the remaining 6 papers out of 25 (Oosterbeek et al, 2004;Yilmaz and Alper, 2019;Cochard et al, 2021;Markowsky and Beblo, 2022;Im and Chen, 2022;Marini, 2023) mostly implement traditional meta-analyses, given the suitability of the latter for explaining heterogeneity in Böckenholt, 2017) when conclusively summarizing multiple studies in the same manuscript. They are instead called single-project meta-analyses when self-contained and the included studies are published as separate papers.…”
Section: Literature Review and Methodologymentioning
confidence: 99%